Features of technical and tactical actions of highly skilled athletes at swimming of competitive distances of 50, 100 and 200 meters way to crawl on his back - Olga Pilipko (Слобожанський науково-спортивний вісник, 2014)
Purpose: to identify the features of technical and tactical actions of highly skilled athletes, specializing in swimming crawl on way back to the distances of different lengths. Material and Methods: we used analysis of scientific and methodical literature, teacher observation, video, timing, methods of mathematical processing of the data. Collection of digital material was carried out during the Championship and Cup of Ukraine on swimming. Surveyed group consisted of participants of the final swim at distances of 50, 100 and 200 meters way to crawl on his back. Results: characterized by changes of speed, tempo and "step" cycle paddle movements in the process of overcoming competitive distances of 50, 100 and 200 meters way to crawl on his back, given their comparative characteristics. Conclusions: the nature of the technical and tactical actions of highly skilled athletes, specializing in swimming crawl on way back, depending on the length of competitive distance.